Ice Storage Studies of Kati (Pellona sp.) - GARG, D K; STEPHEN, JOSE (Fishery Technology, 2017)
Studies were carried out on the effect of ice storage on the composition of kati (Pellona sp.). On the basis of biochemical, bacteriological and organoleptic evaluations, it was observed that kati can be stored in ice for a period of 9 days without appreciable loss in overall quality